The role of governance in rationalizing the expenses of the local collectives as a strategy for preserving public funds (Journal of Economic Additions, 2020)
This article aims to shed light on the financial governance mechanisms, that guarantee the spending rationalization and the use of public funds and its preservation from local corruption. Considering that the ineffectiveness of local expenses, excessive public spending, and weak oversight and corruption are among the most important barriers to reaching local development programs, and improving the economic and the social situations of local communities. In this study, we relied on the descriptive approach to define the conceptual aspect of governance and local collectives, we also used the analytical approach in order to analyze data related to the research topic. The study concluded that there is a strong complementarity between good governance and rationalization of public spending. Where the state can be characterized by a rational and ideal financial policy if the competent authorities attempt to prepare and implement the general budget of the state to activate the principles of good governance and apply it on the ground.Keywords: Governance; Local public expenses; Public spending rationalization; Maintaining public money.